2011
DOI: 10.1093/neuonc/nor077
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic mebendazole shows survival benefit in 2 preclinical models of glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive brain cancer, and despite treatment advances, patient prognosis remains poor. During routine animal studies, we serendipitously observed that fenbendazole, a benzimidazole antihelminthic used to treat pinworm infection, inhibited brain tumor engraftment. Subsequent in vitro and in vivo experiments with benzimidazoles identified mebendazole as the more promising drug for GBM therapy. In GBM cell lines, mebendazole displayed cytotoxicity, with half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
205
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(207 citation statements)
references
References 39 publications
2
205
0
Order By: Relevance
“…We note that these therapeutic effects are not as robust as those obtained previously in the same model (63% increase in survival for mice treated with 50 mg/kg of mebendazole). A major factor that likely contributes to the difference in therapeutic efficacy is that in our study, treatment was started much later (10 d) after tumor cell implantation than in the previous study (5 d) (24). In addition, the GL261 cells used in our study appear to be significantly more aggressive, as the control mice survived for a significantly shorter time, even though fewer tumor cells were implanted.…”
Section: Disclosurementioning
confidence: 61%
See 2 more Smart Citations
“…We note that these therapeutic effects are not as robust as those obtained previously in the same model (63% increase in survival for mice treated with 50 mg/kg of mebendazole). A major factor that likely contributes to the difference in therapeutic efficacy is that in our study, treatment was started much later (10 d) after tumor cell implantation than in the previous study (5 d) (24). In addition, the GL261 cells used in our study appear to be significantly more aggressive, as the control mice survived for a significantly shorter time, even though fewer tumor cells were implanted.…”
Section: Disclosurementioning
confidence: 61%
“…Dosing for mebendazole is less extensively documented in the literature. In one study, daily oral administration of mebendazole at 50 mg/kg was shown to be well tolerated, whereas a dose of 100 mg/kg showed apparent toxicity, as indicated by weight loss (9). However, as our pilot experiments did not reveal any toxicity at the higher dose of 100 mg/kg, we included both 50 mg/kg and 100 mg/kg in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar antitumor activity of mebendazole was found in gastric cancer, medulloblastoma, glioblastoma, leukemia and myeloma as well as in breast cancer stem cell-like cells [22][23][24][25][26]. Mebendazole potently inhibited hedgehog (Hh) signaling and slowed the growth of Hh-driven human medulloblastoma cells at clinically attainable concentrations [27].…”
Section: Anticancer Activity Of Mebendazolementioning
confidence: 59%
“…Mebendazole can be administered with the non-steroidal anti-inflammatory drug sulindac for prevention of tumor initiation in a colon cancer model [33]. Colon Cancer [52] Breast Cancer Triple [29] Breast Cancer [53] Adrenocortical Cancer [19] Adrenocortical Cancer [39] Leukemia/Myeloma [25] Leukemia/Myeloma [34] Leukemia/Myeloma [59,64] NSCLC [20] NSCLC [36] Lung Cancer CSC [57] Cell Lines [9] Cancer stem cells [46] Cancer [61] Gastric Cancer [22] Osteosarcoma [37] Medulloblastoma [23] Prostate Cancer [36] Melanoma [21,29] Ovarian Cancer/ TICs [41 -44] Ovarian cancer [62] Breast CSC-like Cells [26] Breast CSC-like Cells [40] Breast CSC-like Cells [56] Glioblastoma [24,32] Glioblastoma [33] Glioblastoma CD133 + [60] This table lists reports on investigations employing mebendazole, niclosamide and pyrvinium (pamoate) as anticancer agents against cell lines or in experimental animal models.…”
Section: Anticancer Activity Of Mebendazolementioning
confidence: 99%